Corruption and government: causes, consequences, and reform - Rose-Ackerman, Susan (Cambridge Univ. Press, 1999)
"This book suggests how high levels of corruption limit investment and growth can lead to ineffective government. Developing countries and those making a transition from socialism are particularly at risk, but corruption is a worldwide phenomenon. Corruption creates economic inefficiencies and inequities, but reforms are possible to reduce the material benefits from payoffs. Corruption is not just an economic problem, however; it is also intertwined with politics. Reform may require changes in both constitutional structures and the underlying relationship of the market and the state. Effective reform cannot occur unless both the international community and domestic political leaders support change. No single 'blueprint' is possible, but the primary goal should be to reduce the gains from paying and receiving bribes, not simply to remove 'bad apples'. Winner of the the Charles H. Levine 2000 Book Award." http://www.loc.gov/catdir/description/cam029/98043631.html